Pengaruh Pertumbuhan Aset dan Struktur Modal Terhadap Profitabilitas Perusahaan Pada PT. Asuransi Buana Independent - Dio Rahma Fauzi; Ana Ramdhayanti; Usran Masahere (International Forum of Researchers and Lecturers, 2023)
This study aims to examine the effect of asset growth and capital structure on profitability either simultaneously or partially. The population in this study are several employees of PT. Asuransi Buana Independent, totaling 97 people, the selection of the research sample was based on the slovin sampling technique with random sampling. And the data analysis method used is descriptive and multiple linear regression analysis, the results of this study show that the regression equation is the Profitability value Y = 4,548 asset growth and 6,479 capital structure. The results of this test show that asset growth has a significant effect on profitability, and also capital structure has a significant effect on profitability because the tcount is greater than ttable.